Congenital absence of the vas deferens with hypospadias or without hypospadias: Phenotypic findings and genetic considerations - Fang, Jianzheng; Wang, Xiaoyi; Sun, Xueping; Cui, Yugui; Diao, Feiyang; Yang, Xiaoyu (Frontiers in Genetics, 2022)
Congenital absence of the vas deferens (CAVD) is a major cause of obstructive azoospermia. Mutations of CFTR and ADGRG2 cause the majority of CAVD. Despite this, 10%–20% of CAVD patients remain without a clear genetic diagnosis. Herein, the CFTR and ADGRG2 genes were first sequenced using Sanger sequencing in 50 CAVD patients. Whole-exome sequencing (WES) was used to further identify potential novel genetic causes in CAVD with hypospadias. In total, 29 of 50 CAVD patients carried at least one CFTR mutation, but no ADGRG2 mutation was found. 5T was found to be the most frequent variant in our CAVD populations. Seven CAVD patients with hypospadias were further analyzed using WES. No homozygous or compound heterozygous mutations related to disorders of sex development (DSDs) or male infertility were identified by WES. CAVD with hypospadias presented lower testicular volume (9.71 ± 2.14 ml vs. 14.45 ± 2.93 ml, p < 0.001) and higher FSH level (FSH: 7.28 ± 3.91 IU/L vs. 4.24 ± 1.96 IU/L, p = 0.027) than CAVD without hypospadias. It is worth noting that neither CFTR or ADGRG2 mutation nor homozygous or compound heterozygous gene mutations were identified in seven CAVD cases with hypospadias. However, nine heterozygous or hemizygous mutations were selected as potential pathogenic genes in CAVD with hypospadias. In conclusion, CFTR variants, especially 5T, play a major role in the Chinese CAVD population. CAVD with hypospadias shows relatively lower testicular spermatogenesis, suggesting a different genetic basis or pathogenic factor from cystic fibrosis/CAVD or unilateral renal agenesis/CAVD.